Molecular cell biology - 4 0 16; Lodish, Harvey F.;Darnell, James E.; 5 (New York : Scientific American Books :;Distributed by W.H. Freeman and Co., 1995)
This edition features: new chapters on recombinant DNA technology and genetic analysis; discussions of new techniques, including electrophoretic mobility shift assays, DNA footprinting, gene replacement and transgenic animals; and expanded coverage of developmental genetics.
Pt. 1. Laying the groundwork -- The dynamic cell -- Chemical foundations -- Protein structure and function -- Nucleic acids, the genetic code, and protein synthesis -- Cell organization, subcellular structure, and cell division -- Manipulating cells and viruses in culture -- Recombinant DNA technology -- Genetic analysis in cell biology -- Pt. 2. Control of cellular activity by the nucleus -- The molecular anatomy of genes and chromosomes -- DNA replication, repair, and recombination -- Regulation of transcription initiation -- Transcription termination, RNA processing, and posttranscriptional control -- Gene control in development -- Pt. 3. Building and fueling the cell -- Membrane structure: the plasma membrane -- Transport across cell membranes -- Synthesis and sorting of plasma membrane, secretory, and lysosomal proteins -- Cellular energetics: formation of ATP by glycolysis and oxidative phosphorylation -- Photosynthesis -- Organelle biogenesis: the mitrochondrion, chloroplast, peroxisome, and nucleus -- Pt. 5. Integrative and specialized cellular events -- Cell-to-cell signaling -- Nerve cells -- Microfilaments: cell motility and control -- Microtubules and intermediated filaments -- Multicellularity: cell-to-cell and cell-matrix interactions -- Regulation of the Eukaryotic cell cycle -- Cancer -- Immunity.
Second edition's main entry under the heading for Darnell.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Cytology.;Molecular biology.;Cells. -- 20; 20; 2